Implementasi Keteladanan Pemimpin Rohani Berdasarkan Filipi 2: 1-8 Bagi Gembala Gereja Pentakosta Di Papua Klasis Mimika - Fransiscus Xaferius Wanggai; Sutikto Sutikto; Roberth Ruland Marini (Manna Rafflesia, 2021)
The main problem in this research is the example of spiritual leaders when shepherding the congregation. Some of the factors that make the pastor not an example are repentance, character, and minimal human resources. This study applies a qualitative method. The researcher uses the Bible as the main source, also uses literature from several sources of books and journals, to get a clear picture of the example of spiritual leaders based on Philippians 2:1-8, which will later be implemented in the leadership of the pastoral congregation of the Pentecostal Church in Tanah Papua (GPDP). Special Mimika Classics. The results of the study show that in Christian leadership, the pastor as the leader of the local congregation can influence the people he leads. Philippians 2:1-8 is Paul's writing that teaches about the example of Jesus Christ as a spiritual leader, which can be seen from principles, ministry, and personality.